Environmental inequalities in the municipality of Lisbon: Spatial analysis of combustion gases - Silva, C. F. da.; Nunes, N.; Moro, S.; Henriques, J.; Sousa, A.; Sarroeira, R. (Transportation Research Procedia, 2023)
Some inducing factors of climate change can be attributed to a set of pollution indicators, and the territorial distribution of pollution has repercussions on environmental inequalities. Based on the case study of Lisbon, we map some environmental inequalities and how they relate to the location of transport infrastructures, green spaces, and mobility practices. How is air pollution distributed inside Lisbon? What is the relationship between the distribution of air pollution and the location of transport infrastructure, and green spaces? The results show that there are environmental inequalities, air pollution is higher in zones with a dense road network and heavy traffic. Environmentally friendly mobility practices do not exclude an exposure to higher levels of air pollution due to combustion gases, representing a mismatch between the production of pollution and environmental exposure.